THREE-DIMENSIONAL X-RAY TOMOGRAPHIC ANALYSIS OF SINGLE- AND BILAYER TIO2 PHOTOANODES FOR DYE-SENSITIZED SOLAR CELLS (Eureka Journal of Physical and Chemical Research, 2026)
Three-dimensional structural characteristics of TiO₂ photoanodes play a crucial role in determining the performance of dye-sensitized solar cells (DSSCs). In this work, single-layer and bilayer TiO₂ photoanodes were comparatively investigated using industrial microfocus X-ray tomography. The approach enabled volumetric visualization of internal architecture, thickness distribution, interfacial integrity, and defect formation not accessible by conventional two-dimensional techniques.
Keywords: Dye-sensitized solar cells; TiO₂ photoanode; X-ray tomography; Thickness uniformity; Structural defects; Charge transport